Apo Lipoprotein A1 Gene Polymorphisms Predict Cardio-Metabolic Risk in South Asian Immigrants. Issue 1 (23rd May 2013) - Dodani, Sunita; Henkhaus, Rebecca; Dong, Lei; Butler, Merlin G.
Abstract : Objectives : Coronary artery disease (CAD) is a leading cause of death globally with increasing burden in South Asians in the US. Specific genetic variants that influence CAD have not been fully assessed in South Asian Immigrants. The goal is to identify Apo lipoprotein A1 ( APOA1 ) gene polymorphisms and their association with CAD risk factors, metabolic syndrome and dysfunctional HDL (Dys-HDL). Methods : A community-based study on South Asians aged 35-65 years without CAD was conducted. APOA1 gene sequencing was performed and genotypes compared with cardiovascular findings. Results : The prevalence of metabolic syndrome and dysfunctional-HDL was 29.7% and 26%, respectively. Six novel APOA1 gene single nucleotide peptides (SNPs) were analyzed. Three of the six SNPs (G2, G3, and G5) were found to be associated with metabolic syndrome; G2 (T655C) ( p =0.044), G3 (T756C) ( p =0.037) and G5 (T1001C) ( p =0.037). APOA1 gene SNP G1 (T319C) was highly correlated with low HDL levels ( p =0.001). In our study, both associations of APOA1 SNPs with metabolic syndrome and low HDL remained after age-adjustment. Conclusion : Discovery of novel gene polymorphisms will help to understand further the causes of excess CAD risk in South Asians so that preventative strategies targeted to high-risk group can be developed.